The Effect of Model Two Stay Two Stray on Student Learnt Competencies on Ecosystem at Senior High School 4 Pariaman - Nengsih Oktari; Ristiono Ristiono; Zulyusri Zulyusri; Heffi Alberida (Universitas Negeri Padang, 2019)
This research aims to find out the effect of Two Stay Two stray model towards students' learning competencies, which still below from the average and there have no learning process that pursue the students to be active and creative until the students can increase their learning competencies; knowledge, attitude and skill in learning process. The research was quasi-experimental reserach with control group post-test only design. The population of this research was X IPA grade students that devided into five classes at SMAN 4 Pariaman in academic year 2018/2019. The sample was taken by purposive sampling technique which grade X IPA3 as the experimental group and grade X IPA1 as the control group. The result of this research showed the average score for grade X IPA3 was (75,43) for experimental group and (67,57) for control group in students' learning competencies. Then for behavioural competence the average score in experimental group was (84,21) and the control group reached (81,86) which the data was distributed normally and variant homogeneously. In hyphotesis testing was found by the formula tcount> ttable, learning competency (3,15 > 1,67), behavioural competency (1,76 > 1,67). Based on the result of the study, it can be concluded that the Two Stay Two Stray model give positive effect for the students' learning competencies in ecosystem at SMAN 4 Pariaman.